1965
DOI: 10.2136/sssaj1965.03615995002900030019x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Phosphorus in Tile Drainage Effluent

Abstract: Tile drainage effluent from systems on irrigated land in the San Joaquin Valley of California was analyzed for nitrogen and phosphorus and the quantity of each element found was correlated with the quantity of N and P applied for four different cropping patterns. Large percentages of applied N were found to be lost in tile drainage effluent. Phosphorus losses were not significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1967
1967
2004
2004

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The amount of nitrogen removed as nitrate by the tile system represented approximately 1.5 percent of the nitro gen added to the field. Johnston et al (1965) measured nitrate-nitrogen con centrations of tile effluent under various crops in the San Joaquín Valley of Cali fornia. Individual sample concentra tions ranged from 2 to 440 ppm.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of nitrogen removed as nitrate by the tile system represented approximately 1.5 percent of the nitro gen added to the field. Johnston et al (1965) measured nitrate-nitrogen con centrations of tile effluent under various crops in the San Joaquín Valley of Cali fornia. Individual sample concentra tions ranged from 2 to 440 ppm.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient losses from tile drainage systems were measured by Johnston et al (4). Under irrigation, N compounds were leached from the soil readily while P appeared to be mainly fixed.…”
Section: Introductionmentioning
confidence: 99%
“…The latter was mostly in the soluble form. The California studies 22 showed an order of magnitude of less phosphorus in subsurface drainage waters than that found by Sylvester, as phosphorus quantities of only 0.02--0.48 Ib per acre per year were indicated.…”
Section: Transport Of Phosphorusmentioning
confidence: 78%